Noise and vibration analysis in the diesel engine based on biodiesel usage - Muhammad Zikri, Japri (2022)
Utilization of biodiesel has become one of the major interests in substituting fossil fuel parallel to the implementation of green technology which emphasizes the products to be more environmental-friendly. Nevertheless, despite having various kinds of biodiesel, this does not ensure suitability since the usage could improve or aggravate the engine due to higher combustion effects that further influence the higher level of engine noise and vibration, albeit major modification on the engine is not required. Therefore, this study had been conducted by experimental analysis to investigate the relation of noise and vibration level with biodiesel as a substitution fuel in the single cylinder, direct-injection diesel engine produced from various biodiesel blends, engine speed and engine load. The Root Mean Square (RMS) velocity, Sound Intensity Mapping (SIM) together with Sound Power Level (SPL) analyses were used to indicate the effectiveness of biodiesel in the attenuation of the noise and vibration level generated by the diesel engine. D100, B5, B10 and B20 of Palm Oil Methyl Ester (POME) had been utilized to operate the engine by 1200 to 2160 RPM with the application of engine load varied from 0 to 28 Nm. The measurement of the vibration data was done using the uniaxial accelerometer, while for the noise emission data, a pair of ½ inch of microphones were used. In the vibration aspect, the usage of the B20 blend was found to be the lowest level in almost all conditions tested due to the higher cetane number and oxygen content while the B5 and B10 usage tend to increase the vibration level compared to D100. It also can be noticed that the increment of engine load significantly increases the vibration level while increasing the engine speed does not influence the vibration to be higher since an incomplete combustion occurred which led to a reduction in the rate of pressure rise, thus reducing the vibration level in higher engine speed. In the noise emission analysis, the competitiveness between B20 and D100 could be seen in the low engine speed, where the lowest noise level was obtained by B20 while in the high engine speed, the lowest was obtained by D100. On top of that, the highest location of noise source was recorded at the cylinder head, crank-link components, radiator, flywheel and dynamometer. As can be concluded, the usage of POME as a biodiesel could be owed to the lower vibration and partially reducing the noise generated by the engine. Also, the most significant parameter that could contribute to the decrement of the level was the blend ratio followed by the engine load and engine speed.